PENERAPAN PERSONAL HYGIENE DI FOOD AND BEVERAGE PRODUCT HOTEL FOURPOINTS BY SHERATON BATAM - Isra Maulida Oktavia Pakpahan; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
As people who work around food, a high standard of worker hygiene is required. Employee hygiene must be carried out by making sure to keep workers and their clothes clean by following standard hotel operating procedures. Workers have a responsibility to produce safe food products and good worker hygiene is one of the important things needed to keep food products safe from microbial contamination. This study aims to identify and analyze the process of implementing Personal Hygiene at the Food and Beverage Product Hotel Fourpoints By Sheraton Batam. This study used descriptive qualitative method. The research subjects or respondents in this study used a purposive sampling technique, which was determined based on the person who was considered to know the most about the information needed in the study. The research subjects in this study were all Food and Beverage Product employees, totaling 6 people consisting of: Head Chef, Demi Chef, First Cook and Cook Helper who were involved and related to the procedures for implementing personal hygiene in Food and Beverage Products at Fourpoints By Sheraton Hotel. Batam. Then, how to collect data using Observation, Interview and Documentation. The results showed that the application of Personal Hygiene at the Food and Beverage Product Hotel Fourpoints By Sheraton Batam had been implemented quite well and in accordance with the Standard Operating Procedures that had been made by the Company. However, there are still some Kitchen Employees who have not complied with and properly implemented the Standard Operating Procedures that have been made by the Company. Keywords: Application of Personal Hygiene, Food and Beverage, Hotel FourPoints By Sheraton Batam